Integrating schools in a changing society : new policies and legal options for a multiracial generation - Frankenberg, Erica; Debray, Elizabeth H. (The University of North Carolina Press, 2011)
"In this comprehensive volume, a roster of leading scholars in educational policy and related fields offer eighteen essays seeking to illuminate new ways for American public education to counter persistent racial and socioeconomic inequality in our society. Drawing on extensive research, the contributors reinforce the key benefits of racially integrated schools, examine remaining options to pursue multiracial integration, and discuss case examples that suggest how to build support for those efforts"--Provided by publisher